The general's daughter - DeMille, Nelson; Neufeld, Mace.; Rehme, Robert; Krane, Jonathan D.; West, Simon; Paramount Pictures ([Hollywood, Calif.] Paramount Pictures, 1999)
When the daughter of a well-known and well-respected base commander is raped and murdered, an army sergeant is summoned to look into the matter and finds a slew of cover-ups at West Point.
VHS.
Based on the novel by Nelson Demille.
Stratton Leopold, co-producer ; screenplay by Christopher Bertolini and William Goldman ; produced by Mace Neufeld ; directed by Simon West.
John Travolta, Madeleine Stowe.
Keywords: Murder -- Drama; Mystery -- Feature; Thriller -- Feature